Use of a Sec signal peptide library from Bacillus subtilis for the optimization of cutinase secretion in Corynebacterium glutamicum. Issue 1 (December 2016) - Hemmerich, Johannes; Rohe, Peter; Kleine, Britta; Jurischka, Sarah; Wiechert, Wolfgang; Freudl, Roland; Oldiges, Marco
Abstract Background Technical bulk enzymes represent a huge market, and the extracellular production of such enzymes is favorable due to lowered cost for product recovery. Protein secretion can be achieved via general secretion (Sec) pathway. Specific sequences, signal peptides (SPs), are necessary to direct the target protein into the translocation machinery. For example,  >150 Sec-specific SPs have been identified forBacillus subtilis alone. As the best SP for a target protein of choice cannot be predicted a priori, screening of homologous SPs has been shown to be a powerful tool for different expression organisms. While SP libraries between closely related species were successfully applied to optimize recombinant protein secretion, this was not investigated for distantly related species. Therefore, in this study a Sec SP library from low-GC firmicutesB. subtilis is investigated to optimize protein secretion in high-GC actinobacteriumCorynebacterium glutamicum using cutinase fromFusarium solani pisi as model protein. Results A homologous SP library (~150 SP) for recombinant cutinase secretion inB.  subtilis was successfully transferred toC.  glutamicum as alternative secretion host. Cutinase secretion inC.  glutamicum was quantified using an automated micro scale cultivation system for online growth monitoring, cell separation and cutinase activity determination. Secretion phenotyping results were correlated to those from a previous study, in which the same SP library was used to optimize secretion of the same cutinase but usingB. subtilis as host. Strikingly, behavior of specific SP-cutinase combinations was changed dramatically betweenB.  subtilis andC.  glutamicum . Some SPs showed comparable cutinase secretion performances in both hosts, whereas other SPs caused diametrical extracellular cutinase activities. Conclusion The optimal production strain for a specific target protein of choice still cannot be designed in silico. Not only the best SP for a target protein has to be evaluated each time from scratch, the expression host also affects which SP is best. Thus, (heterologous) SP library screening using high-throughput methods is considered to be crucial to construct an optimal production strain for a target protein.